Critical literacy of young citizens in the digital era - Nurjanah, Nunung; Abdulkarim, Aim; Komalasari, Kokom; Bestari, Prayoga; Suwandi, Mohamad Ardin (Jurnal Civics: Media Kajian Kewarganegaraan, 2024)
Today's young citizens are categorised as Generation Z. They are very closely related to gadgets and are often called digital natives. Currently, the number of young citizens dominates the Indonesian population, so young citizens need critical literacy to respond to any information critically. This study aimed to determine the level of critical literacy of young citizens. The research approach is descriptive and quantitative, with data collected using a survey questionnaire from senior high school students in Indramayu Regency, Indonesia. The research results are as follows: making decisions based on data is classified as excellent at 70%; being communicative and tolerant of differences at 73.1%; taking concrete action for a better life for all is 33.7%. Based on these findings, critical literacy needs to be continuously improved, including the use of learning resources and learning media that encourage the use of digital technology.